Relevansi Nusyuz Suami Dalam Perkara Perceraian (Studi Putusan 2472/Pdt.G/2023/PA.Lmg dan 257/Pdt.G/2020/PA.Mtr) - Nadhira Wahyu Adityarani; Nathania Permata S (Jurnal JURISTIC, 2025)
This study examines the concept of husband's nusyuz in Islamic family law and its relevance as a valid reason for divorce in Religious Courts. While nusyuz has often been associated exclusively with wives, contemporary approaches suggest that husbands can also commit nusyuz when they neglect their household obligations, such as failing to provide maintenance, committing violence, or abandoning their wives without just cause. This study uses a normative-empirical legal method with a statutory, conceptual, and sociological approach. The study focuses on the analysis of two court decisions, namely Decision Number 2472/Pdt.G/2023/PA.Lmg and Decision Number 257/Pdt.G/2020/PA.Mtr, which indicate that a husband's actions that violate his wife's rights have been recognized as grounds for divorce even though they are not explicitly stated as nusyuz. The results of this study confirm that husband's nusyuz can be used as a legal basis in a divorce suit by a wife, in accordance with the provisions of Article 39 paragraph (2) of Law Number 1 of 1974 and Article 116 of the Compilation of Islamic Law. This finding also contributes to a renewed perspective on Islamic family law, focusing on fairer and more equal treatment.